Validation of a Malay Version of the Smartphone Addiction Scale among Medical Students in Malaysia - Ching, Siew Mooi; Yee, Anne; Ramachandran, Vasudevan; Sazlly Lim, Sazlyna Mohd; Wan Sulaiman, Wan Aliaa; Foo, Yoke Loong; Hoo, Fan kee (PLOS ONE, 2015)
Introduction This study was initiated to determine the psychometric properties of the Smart Phone Addiction Scale (SAS) by translating and validating this scale into the Malay language (SAS-M), which is the main language spoken in Malaysia. This study can distinguish smart phone and internet addiction among multi-ethnic Malaysian medical students. In addition, the reliability and validity of the SAS was also demonstrated. Materials and Methods A total of 228 participants were selected between August 2014 and September 2014 to complete a set of questionnaires, including the SAS and the modified Kimberly Young Internet addiction test (IAT) in the Malay language. Results There were 99 males and 129 females with ages ranging from 19 to 22 years old (21.7±1.1) included in this study. Descriptive and factor analyses, intra-class coefficients, t-tests and correlation analyses were conducted to verify the reliability and validity of the SAS. Bartlett’s test of sphericity was significant (p <0.01), and the Kaiser-Mayer-Olkin measure of sampling adequacy for the SAS-M was 0.92, indicating meritoriously that the factor analysis was appropriate. The internal consistency and concurrent validity of the SAS-M were verified (Cronbach’s alpha = 0.94). All of the subscales of the SAS-M, except for positive anticipation, were significantly related to the Malay version of the IAT. Conclusions This study developed the first smart phone addiction scale among medical students. This scale was shown to be reliable and valid in the Malay language.